Hypoglycemic and Antioxidative Effects of Anacardium Occidentale Linn.In Diabetic Rats - Ling, Letty (2006)
Diabetes mellitus is found to be associated with oxidative damage which coexists with a reduction in the antioxidant status. The Malay folklore medicine in Malaysia believes that by consuming the decoction of the vein and leaves (vascular bundle) of A. occidentale L. (cashew-nut), it is able to lower blood glucose level of diabetic patients. The objective of this study was to verify the potential hypoglycemic and antioxidative effects of Anacardium occidentale L.leaves aqueous extract (AOE) in Type 2 diabetes rat model.Freeze-dried AOE of various doses (50 mg/kg, 250 mg/kg, 500 mg/kg and 1000 mg/kg body weight) were administered to streptozotocin induced Type 2 diabetic rats. The rats were force-fed with the extracts once daily for six weeks. Oral glucose tolerance test (OGTT) with 1.5 g/kg body weight of glucose challenge was then conducted to monitor the serum glucose level.Blood was collected through cardiac puncture to examine the levels of lipid peroxidation and the enzymatic activities in the experimental rats.The result showed an improvement in the glucose tolerance after six weeks of treatment significantly as compared to the diabetes control (P<0.05). After treatment, the rats treated with AOE at all doses have lower fasting glucose levels compared to the pre-treatment week.It was also noticed that all the doses of the leaves extract managed to delay the rise of glucose level in oral glucose tolerance curve.Thus,A. occidentale leaves aqueous extract had suppression effect on the increase of serum glucose levels in oral glucose load. The AOE at all doses exhibited low lipid peroxidation product indicated by serum malondialdehyde (MDA) levels after six weeks of extract administration as compared to the pre-treatment week. The reduced MDA levels of group treated with AOE 250mg/kg, AOE 500 mg/kg and AOE 1000mg/kg are comparable to the MDA levels as obtained by the normal control groups after six weeks of extract treatment. Serum catalase activities were found to be significantly elevated in diabetic groups treated with AOE as compared to the diabetic control groups whereas in the normal groups, the serum catalase activities in blood were much higher than the diabetic groups.Plasma superoxide dismutase (SOD) activities of AOE treated were found to be higher than the diabetes control after three weeks of administration. The SOD activities were higher than the normal groups significantly (P<0.05).However,there were reductions on SOD activities at Week 6. Diabetes treated groups (AOE 50 mg/kg, AOE 250 mg/kg and AOE 500 mg/kg) showed an increased of plasma gluthathione peroxidase (GPx) activities at Week 3 as compared to the pre-treatment groups.Histological study of the pancreas showed an extensive damage of the islets of Langerhans and reduced dimensions of islet in the diabetic-induced rats.There were significant increase in the area, perimeter and diameter of pancreatic islets in both glybenclamide and AOE treated rats.The diabetic rats treated with AOE 250 mg/kg have the highest increase in area, perimeter and diameter of the islet of Langerhans and have no significant difference compared to the normal control rats.This may suggest that AOE 250 mg/kg could improve and protect the islet Langerhans cells from oxidative degeneration resembling the normal rats. The results of this study indicate that A. occidentale L. leaves might possess hypoglycemic activity.The alterations of the enzymatic antioxidant activities in the experimental animals provides evidence that the preventive effects of A. occidentale L.may be due to inhibition of lipid peroxidation by its antioxidant properties.Thus, A. occidentale L.possesses antioxidant properties which counteract the oxidative damage in diabetic subjects.